Personality and trajectories of posttraumatic psychopathology: A latent change modelling approach. (August 2016) - Fletcher, Susan; O'Donnell, Meaghan; Forbes, David
Highlights: Survivors of recent trauma can be categorised into three personality typologies. These typologies display different patterns of posttraumatic disorder onset. A personalised medicine approach to early intervention is recommended. Personality-based, transdiagnostic interventions may be a useful starting point. Future research should investigate the protective value of low constraint. Abstract: Background: Survivors of traumatic events may develop a range of psychopathology, across the internalizing and externalizing dimensions of disorder and associated personality traits. However, research into personality-based internalizing and externalizing trauma responses has been limited to cross-sectional investigations of PTSD comorbidity. Personality typologies may present an opportunity to identify and selectively intervene with survivors at risk of posttraumatic disorder. Therefore this study examined whether personality prospectively influences the trajectory of disorder in a broader trauma-exposed sample. Methods: During hospitalization for a physical injury, 323 Australian adults completed the Multidimensional Personality Questionnaire—Brief Form and Structured Clinical Interview for DSM-IV, with the latter readministered 3 and 12 months later. Latent profile analysis conducted on baseline personality scores identified subgroups of participants, while latent change modelling examined differences in disorder trajectories. Results: Three classes (internalizing, externalizing, and normal personality) were identified. The internalizing class showed a high risk of developing all disorders. Unexpectedly, however, the normal personality class was not always at lowest risk of disorder. Rather, the externalizing class, while more likely than the normal personality class to develop substance use disorders, were less likely to develop PTSD and depression. Conclusions: Results suggest that personality is an important mechanism in influencing the development and form of psychopathology after trauma, with internalizing and externalizing subtypes identifiable in the early aftermath of injury. These findings suggest that early intervention using a personality-based transdiagnostic approach may be an effective method of predicting and ultimately preventing much of the burden of posttraumatic disorder.